Exergy and Exergoenvironmental Analysis of a CCHP System Based on a Parallel Flow Double-Effect Absorption Chiller - Ali Mousafarash (International Journal of Chemical Engineering)
A combined cooling, heating, and power (CCHP) system which produces electricity, heating, and cooling is modeled and analyzed. This system is comprised of a gas turbine, a heat recovery steam generator, and a double-effect absorption chiller. Exergy analysis is conducted to address the magnitude and the location of irreversibilities. In order to enhance understanding, a comprehensive parametric study is performed to see the effect of some major design parameters on the system performance. These design parameters are compressor pressure ratio, gas turbine inlet temperature, gas turbine isentropic efficiency, compressor isentropic efficiency, and temperature of absorption chiller generator inlet. The results show that exergy efficiency of the CCHP system is higher than the power generation system and the cogeneration system. In addition, the results indicate that when waste heat is utilized in the heat recovery steam generator, the greenhouse gasses are reduced when the fixed power output is generated. According to the parametric study results, an increase in compressor pressure ratio shows that the network output first increases and then decreases. Furthermore, an increase in gas turbine inlet temperature increases the system exergy efficiency, decreasing the total exergy destruction rate consequently.